METODE PENENTUAN AWAL WAKTU SALAT DALAM PERSPEKTIF ILMU FALAK - Ismail Ismail (Islam Futura, 2015)
Astronomy is a science which studies the trajectory of celestial objects such as the Earth, the moon, the sun and the stars in order to understand the direction and the time at the Earth's surface for the sake of worshiping. The determination of the early time of prayer time is the scope of astronomy. In this study, the issues be studied is the effect of altitude and the brilliance of the sky in determining the prayers' times. To answer the problems, the writer used descriptive qualitative method and normative approach. This approach is necessary because of the emergence problem on the results of the completion on the calculation formulas of the prayers' time which is one of the most important worship and the attributes if Islam. The results of the research find that altitude is greatly affect the results of the initial calculation of Maghrib, Isya, and Subuh. While, the brilliance of the sky affects the initial prayer time of Isya and shubuh.